State of the Art : Current Acetabulum Fracture Management - Ismail Hadisoebroto Dilogo; Bernadus Riyan Hartanto; Milton Lee Chip Routt (Indonesian Hip and Knee Society (IHKS), 2022)
The annual incidence of acetabulum fractures is estimated to be 8.1 per 100.000 patients. In young adults, high energy trauma is the primary mechanism, but in the elderly, low energy trauma is the primary mechanism. Comorbidities, poor bone quality, and delayed presentation are all linked to a poor outcome. From diagnosis to treatment, the goal of this study is to describe the required procedures in reaching a satisfactory result.It is essential to be able to correctly classify acetabular fractures using the Joudet and Letournel classifications, especially when planning definitive therapy. Non-surgical and operative treatment methods are available for acetabulum fractures. All acetabulum fractures that result in hip joint instability and/or incongruity require surgical treatment. Although the prognosis is lower than in younger patients, Open Reduction Internal Fixation (ORIF) remains the mainstay of therapy for most elderly acetabular fractures. Central fracture dislocation of the hip with medial migration of the quadrilateral plate is common in patients with both column, transverse, T-shaped, and anterior column-posterior hemi-transverse fractures. Failure to repair the quadrilateral plate will result in an incongruent hip and a poor outcome since it has a thin medial wall that fractures with less force than the superior weight-bearing portion of the acetabulum.The goals of postoperative care are to maximize the patient's function, allow a quick return to function, and detect early problems. Complications with acetabulum fractures might occur with any treatment option. Post-traumatic arthritis is the most common complications, followed by Deep Vein Thrombosis (DVT), heterotrphic ossification, infection, and iatrogenic sciatic nerve damage.